Optimizing Diversion Policy Due to Overcrowding in Children's Special Development Institutions (LPKA) - Hamdi Hasibuan; Adi Mansar; Surya Perdana (Faculty of Law, Universitas Pekalongan, 2023)
Child convicts are separated from adult convicts so that they are placed in the Special Children's Development Institution (LPKA), where this is a place for child convicts, not as a place to administer punishment as we know in Correctional Institutions (Lapas) which contain adult convicts. The essence of diversion with a restorative justice approach is the